Women artists in the 20th and 21st century - Grosenick, Uta; Becker, Ilka (Taschen, 2005)
It's a women's world (TASCHEN's 25th anniversary special edition) Many of the century's greatest artistic talents grace the pages of this tome, each artist represented by six pages of illustrations and photographs covering the various phases of her life and work, including biographical portraits and text.